APLIKASI TEORI UMPAN BALIK (FEEDBACK) DALAM PEMBELAJARAN MOTORIK PADA ANAK USIA DINI - Windarsih, Chandra Asri (IKIP Siliwangi, 2016)
Children every day grow by magic, physically and mentally. Children in the process of learning motormovement skills need serious attention, it is because this is the forerunner of further development, for the future, for the motor development of children in the future until he becomes an adult. Motor development if honed and directed would be optimal. Motor development means development that involves the physical movement of a person related to muscles and senses. Physical development of the child's motor will be able to develop properly if given stimulation and good nutrition factor. The development of a child would be maximized if there are aspects of his supporters, one aspect of the supporters was the feedback (feedback) either intrinsic (from within the child himself / private) or by extrinsic (external factors as support). Motor development of children if given feedback (feedback) ektrinsik itself intrinsic feedback will arise and have a relationship that is not unexpected. Children will learn to correct itself with the help of mentors so that the achievement of motor learning will be optimal.Keywords: motor learning, application, feedback, early childhoodÂ